Photochromic properties of tungstate-based glasses - Poirier, Gael; Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2007)
Vitreous samples were prepared in the NaPO(3)-BaF(2)WO(3) ternary system with high WO(3) concentrations. These glasses exhibit a strong absorption in the visible due to the presence of reduced tungsten species and the use of oxidizing species is required. The couple Sb(2)O(3)/NaNO(3) was introduced in the composition and allowed to obtain transparent glasses. These oxidized samples were illuminated by visible laser radiation and showed an efficient volumetric photochromic effect. The photosensitive effect appeared as a dark spot throughout the entire volume of the glasses. The effect was investigated by several techniques such as, U-V-visible absorption, Raman and XANES at the L(1) and L(3) tungsten absorption edges. The results suggest a photoreduction of tungsten atoms without structural changes of the viteous network. Finally, the photochromic effect can be erased by thermal treatment at 200 degrees C for a few minutes. (C) 2007 Published by Elsevier B.V.
Keywords: glass; tungsten; photochromic